Are Breast Cancer Molecular Classes Predictive of Survival in Patients with Long Follow-Up?. Issue 6 (30th October 2013) - Pracella, Danae; Bonin, Serena; Barbazza, Renzo; Sapino, Anna; Castellano, Isabella; Sulfaro, Sandro; Stanta, Giorgio
Abstract : In this study we investigate the clinical outcomes of 305 breast cancer (BC) patients, aged 55 years or younger, with long follow-up and according to intrinsic subtypes. The cohort included 151 lymph node negative (LN−) and 154 lymph node positive (LN+) patients. Luminal A tumors were mainly LN−, well differentiated, and of stage I; among them AR was an indicator of good prognosis. Luminal B and HER2 positive nonluminal cancers showed higher tumor grade and nodal metastases as well as higher proliferation status and stage. Among luminal tumors, those PR positive and vimentin negative showed a longer survival. HER2-positive nonluminal and TN patients showed a poorer outcome, with BC-specific death mostly occurring within 5 and 10 years. Only luminal tumor patients underwent BC death over 10 years. When patients were divided in to LN− and LN+ no differences in survival were observed in the luminal subgroups. LN− patients have good survival even after 20 years of follow-up (about 75%), while for LN+ patients survival at 20 years (around 40%) was comparable to HER2-positive nonluminal and TN groups. In conclusion, in our experience ER-positive breast tumors are better divided by classical clinical stage than molecular classification, and they need longer clinical follow-up especially in cases with lymph node involvement.